The Effect of Light Colour During Night Time to Sleep Quality - Sylvanus, Peter; Lumbuun, Nicolaski (Medicinus, 2020)
Introduction: Sleep is one of the basic human needs, where human uses one third of their time only for sleeping. Some contributing factors towards bad sleep quality are stress, depression, surrounding noise, and the use of a bright light. It is known that white lights cause the activation of melanopsin, causing circadian cycle shift, whereas using yellow light does not. The aim of this research was to analyze whether there is an effect of using either white or yellow light towards sleep qualityMethod: This is RCT on 81 subjects. Sleep quality was measured using PSQI questionnaire on 3 measurements with each measurement taken every week. Result of the analyzed data using the General Linear Model – Repeated Measurement (GLM-RM) method Result: There were significant differences on PSQI score between group that used white light during sleep (7.6 ± 2.3) in comparison to the control group (5.2 ± 1.8) (p = 0.02), but result also showed that there were no significant difference between the group that used yellow light (6.1 ± 1.7) during sleep in comparison with the control group (p = 0.14). Conclusion: There is a significant difference between the uses of white lights during sleep towards sleep quality, but there has not been any significant difference between the uses of yellow light during sleep towards sleep quality